Gender-and age-specific associations of sleep duration and quality with cognitive impairment in community-dwelling older adults in Anhui Province, China - Liu, Xuechun; Xu, Peiru; Wei, Rong; Cheng, Beijing; Sun, Liang; Yang, Linsheng; Chen, Guihai (Frontiers in Public Health, 2024)
Objective: To examine associations of sleep duration and quality with cognitive impairment in older adults and the moderating role of gender and age in these associations.: This community-based cross-sectional study included 4,837 participants aged 60 years and above. Cognitive function was assessed using the Chinese version of the Mini-Mental State Examination (MMSE), and the participants were grouped based on the presence of cognitive impairment. The duration and quality of sleep were assessed using the Pittsburgh Sleep Quality Index (PSQI). Multivariate logistic regression models were used to analyze associations of sleep duration and quality with cognitive impairment. The role of age and gender in these associations have also been explored.The age (mean ± SD) of the participants was 71.13 ± 5.50 years. Of all older adults, 1,811 (37.44%) were detected as cognitive impairment, and 1755(36.8%) had poor sleep quality. Among those with cognitive impairment, 51.09% were female. The proportion of the participants with cognitive impairment is significantly higher in those with symptoms of depression (49.73%, 273/549) (χ 2 =41.275, P<0.001) than in those without depressive symptoms. After adjustment for multiple confounding factors and the crucial covariate (depressive symptoms), the odds ratios(OR) (95% confidence interval [CI]) of cognitive impairment (with 7-7.9 hours regarded as the reference group) for individuals with a sleep duration of <6, 6-6.9, 8-8.9, and ≥9